Revitalisation Function of The Kasalasa Tradition in The Moving Farming of The Muna Tribe as A Sustainable Agriculture Model and Conservation of Natural Resources in Muna District - Rahmat Sewa Suraya; La Ode Alwi; Zulfa Zulfa; Agus Rihu (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
This article discusses the local wisdom of the Muna people, which is reflected in the Kasalasa tradition, a ritual performed before starting agricultural activities. This ritual begins with clearing new land, planting crops, and showing the close relationship between agricultural activities and natural resource conservation. An ethnographic approach was used in this research to understand the farming culture of the Muna people, especially in the context of shifting cultivation. The data presented were qualitative and analysed descriptively to facilitate understanding. The results of the study showed that the Kasalasa Tradition has many values and functions, including norms and customs that are adhered to by farmers as a guide in farming. Revitalising this tradition can become a reference for the Muna people and society in general in supporting sustainable agriculture while still paying attention to the sustainability of natural resources. Maintaining local wisdom, such as the Kasalasa tradition, is essential to ensuring that agricultural practices are sustainable not only from an economic perspective but also from an environmental and socio-cultural one. By strengthening the values and norms contained in this tradition, people can develop agricultural systems that are environmentally friendly and sustainable for the future.